2018
DOI: 10.1016/j.jid.2017.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of Acral Melanoma Based on Site and Relative Sun Exposure

Abstract: Acral melanoma is distinct from melanoma of other cutaneous sites, yet there is considerable variation within this category. To better define this variation, we assessed melanomas occurring on dorsal (n = 21), volar (n = 9), and subungual/interdigital (n = 13) acral skin as well as acral nevi (n = 24) for clinical, histologic, and molecular features. Melanomas on dorsal acral surfaces demonstrated clear differences compared with volar and subungual/interdigital melanomas. The latter two groups exhibited signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 46 publications
(44 reference statements)
3
46
2
Order By: Relevance
“…Among 1157 AM patients, 68.5% of patients were reported as sole melanoma at diagnosis in our study. The constitution percentages of different primary sites were consistent with the reports of Haugh et al and Curtin et al 12,17 With respect to age, the overall median age of the patients at time of diagnosis was 56 and the sole group had an older median/mean age than the other two groups, which is similar to another study result. 17 Nunes et al 10 analyzed 157 Brazilian AM patients; the age at diagnosis was older than ours and the age distribution between palms and nail beds was similar.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among 1157 AM patients, 68.5% of patients were reported as sole melanoma at diagnosis in our study. The constitution percentages of different primary sites were consistent with the reports of Haugh et al and Curtin et al 12,17 With respect to age, the overall median age of the patients at time of diagnosis was 56 and the sole group had an older median/mean age than the other two groups, which is similar to another study result. 17 Nunes et al 10 analyzed 157 Brazilian AM patients; the age at diagnosis was older than ours and the age distribution between palms and nail beds was similar.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, an analysis of 177 AM patients in Korea 11 showed that the ulceration proportion in the subungual group was higher. Haugh et al 12 detected the gene mutational profile in AM patients and found that nail bed melanoma was more likely to have CDK4 copy number aberration and lower frequency of BRAF mutation than melanoma originating on palms. Another report 13 showed that the prevalence of BRAF mutation between palm and other subgroups in AM was similar but the NRAS mutation frequency was significantly higher in palm melanoma.…”
mentioning
confidence: 99%
“…Acral melanoma is rare in Caucasian populations, while it is the most common subtype of melanoma in Asian, African, and Latin American populations [2]. Although several genomic profiling studies of melanoma have been conducted, the numbers of acral melanoma cases in these were limited [11][12][13][14][15]. Furthermore, the genetic heterogeneity of acral melanoma has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant melanoma is classified based on its anatomical site and degree of ultraviolet (UV) light exposure . Acral melanoma (AM) occurs on nonhairy acral skin (palms, soles and nail beds) and is not thought to be linked to UV radiation . Among white people, AMs constitute around 10% of all cases of melanoma.…”
mentioning
confidence: 99%